Hydrocarbon potential in the Northern Egyptian Red Sea: insights from geophysical datasets and analysis of onshore marginal outcrop analogues and subsurface sequences - Ahmed M. Noureldin; Mustafa Hassan; Mohamed Farouk; Walid M. Mabrouk; Ahmed E. Radwan; Ahmed Metwally (Scientific Reports, 2025)
Abstract The Red Sea remains a largely under-explored basin, with the Northern Egyptian Red Sea requiring further investigation due to limited borehole data, sparse case studies, and poor seismic quality. A petroleum system, regional structural cross-section, and geological block diagrams integrating onshore fieldwork from Gebel Duwi and offshore subsurface geology were utilized to assess the hydrocarbon potential of the Northern Egyptian Red Sea (NERS). The findings highlight that pre- and syn-rift organic-rich source units in the NERS could generate oil and gas, similar to the capped reservoirs of the Southern Gulf of Suez. The study also reveals that both regions (NERS and SGOS) were influenced by the Levant-Aqaba transform fault influenced both regions (NERS and SGOS), resulting in southwest-dipping strata, replicating the Northern Gulf of Suez structural style. Additionally, rifting extended the rotated basement faulted blocks from the shoreline to the axial trough, creating wedged Miocene sections. Most offshore boreholes in the Red Sea bottomed in Precambrian rock directly below the syn-rift Miocene sequence, suggesting these wells were off-structure, similar to sidetracked wells in the Gulf of Suez, which successfully captured thick pre- and syn-rift sediments. These insights can drive further advancements in hydrocarbon exploration in the Northern Egyptian Red Sea.